2020
DOI: 10.15694/mep.2020.000092.1
|View full text |Cite
|
Sign up to set email alerts
|

Response and Lessons Learnt Managing the COVID-19 Crisis by School of Medicine, National University of Singapore

Abstract: Background: Healthcare professionals are playing an important role in the recent COVID-19 outbreak. It is crucial that the health systems maintain their ability to train students and residents during this time. However, there is a paucity of literature on the measures taken by higher education institutions to ensure academic continuity. The aim of this article is to share the systematic measures that were taken during the COVID-19 pandemic by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 10 publications
2
30
0
1
Order By: Relevance
“…In Asia, studies reported government enforced lockdowns and restrictive measures, including the closure of medical campuses (Singh et al 2020;Srinivasan 2020;Veasuvalingam and Goodson 2020). Studies in Singapore reported the escalation of the national pandemic alert to Disease Outbreak Response System Condition (DORSCON)-Orange resulting in quarantining, temperature screenings and visitor restrictions at hospitals (Boursicot et al 2020;Kanneganti et al 2020;Samarasekera et al 2020). In Europe, countries implemented national restrictions on non-essential activities, invoked lockdowns and moved all educational activities online (Finn et al 2020;Moszkowicz et al 2020;Torres et al 2020).…”
Section: Geographical Location and Local Covid-19 Specific Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Asia, studies reported government enforced lockdowns and restrictive measures, including the closure of medical campuses (Singh et al 2020;Srinivasan 2020;Veasuvalingam and Goodson 2020). Studies in Singapore reported the escalation of the national pandemic alert to Disease Outbreak Response System Condition (DORSCON)-Orange resulting in quarantining, temperature screenings and visitor restrictions at hospitals (Boursicot et al 2020;Kanneganti et al 2020;Samarasekera et al 2020). In Europe, countries implemented national restrictions on non-essential activities, invoked lockdowns and moved all educational activities online (Finn et al 2020;Moszkowicz et al 2020;Torres et al 2020).…”
Section: Geographical Location and Local Covid-19 Specific Detailsmentioning
confidence: 99%
“…There was only one study considered at low risk of bias and high quality in all five domains (Blake et al 2020). There were a further six studies that whilst not having full reporting of detail, did report in all areas with varying amounts of detail (Brown et al 2020;Buonsenso 2020;Choi et al 2020;Johnston et al 2020;Murdock et al 2020;Samarasekera et al 2020). There were six studies that did not report on any of the five domains that were judged at high risk of bias and low quality for all (Ahmed et al 2020;Boodman et al 2020;Burns and Wenger 2020;Haines et al 2020;Keegan et al 2020;Lubarsky 2020).…”
Section: Quality Of Reporting For the Educational Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Approaches were similar, and there has not yet been sufficient time for institutions to evaluate the impact of their interventions. The key to success appeared to be leadership and communication involving all stakeholders (Samarasekera et al, 2020). Lectures are now online, the use of simulation has increased and strategies for reducing the mixing of patients, students and staff for teaching and assessment are being developed.…”
Section: Resultsmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic, which began in February 2020, has necessitated adaptations in numerous aspects of life around the world, including in medical education. Medical schools should formulate and enact strategies to move learning and assessment fully online, defer other face-to-face and hands-on activities to later dates, prevent undergraduate medical students from conducting their clinical rotations (due to safety reasons), enrich the curriculum with COVID-19 subjects, and attempt to support medical and healthcare professionals working on the front line [1,2].…”
Section: Introductionmentioning
confidence: 99%